HAK NASABAH ASURANSI TERHADAP PERUSAHAAN ASURANSI YANG MENGALAMI KEPALITAN - Mira Gusmawati, (2021)
The purpose of this study is to examine the rights of insurance customers and their legal protection against insurance companies experiencing bankruptcy. This research uses normative legal research methods. The results of this study show that the rights of customers to insurance companies experiencing bankruptcy are regulated in the Insurance Law that the distribution of bankruptcy assets is in accordance with their rights, which is stated in the insurance agreement that was previously agreed. The rights of insurance customers are still guaranteed because it is stated in Article 4 of the Consumer Protection Act. The appointment of curators and supervisory judges as regulated in the Bankruptcy Law is a form of legal protection for policyholders in insolvency insurance companies. Creditors are still protected by law if the insurance company goes bankrupt, because if the agreement is not continued, the creditors can file a lawsuit against the curator. In view of Article 52 paragraph (1) of the Insurance Law where the position of insurance customers is higher than other creditors, namely in the distribution of bankruptcy assets, payment to insurance customers must take precedence. However, in some cases that occur, insurance customers are assigned to concurrent creditors because what takes precedence in making payments is the payment of workers' wages.